(untitled) (Entrepreneurship Journal for Finance and Business, 2024)
The research addresses two main topics: the International Public Sector Standard (IPSAS 24) relating to the presentation of budget information in financial statements, and the Government Financial Management Information System (GFMIS). In relation to IPSAS 24, the research focuses on clarifying how budget information is presented in public sector financial statements. The standard aims to achieve transparency and reliability in providing financial information to governments and government institutions. The research addresses various aspects of the standard, such as defining financial terms, basic principles, and requirements that must be met in submitting the budget. For GFMIS, the research reviews and evaluates this system that is used in managing financial information for governments. GFMIS aims to improve the efficiency and effectiveness of government financial resources management, and facilitate financial planning, monitoring and evaluation processes. The concept of GFMIS, its components and benefits are reviewed, as well as the challenges of its implementation and future preferences for its development and improvement. Overall, the research aims to provide previous researchers with an overview of IPSAS 24 and its importance in presenting budget information in public sector financial statements, as well as reviewing GFMIS and its role in improving government financial information management. This research can contribute to raising public sector awareness of the importance of adhering to international accounting standards in the public sector and using advanced financial information management systems to enhance transparency and effectiveness in managing the financial resources of governments. The main reason for linking these two variables is to enhance transparency, accountability, and financial control in the public sector and ensure that government financial information complies with international accounting standards in the public sector. Therefore, reviewing these two variables and analyzing their role will provide an important theoretical and applied framework for understanding the relationship between them to rationalize the budget. The most important conclusions reached for the review research are that the main goal of applying the (IPSAS) standards is to achieve compatibility in accounting policies at the global level by providing guidance and directives to develop a comprehensive theoretical framework for government accounting. Evaluating government performance is achieved through commitment to applying the (24 IPSAS) standard., which allows the preparation of a variety of financial statements detailing the approved budget and actual expenditures, the final budget (adjusted allocation), and achieving the qualitative characteristics of accounting information. The government unit did not disclose in the financial statements the extent of compliance with legislative and regulatory laws and other regulations imposed by external parties. (The State) As for the recommendations, the researchers suggest that government institutions should commit to implementing the IPSAS 24 standard completely and accurately to ensure compliance with international accounting standards. Government institutions should analyze their actual needs and conduct a feasibility study before making any transfers in the original budget, in order to ensure a strong scientific basis and improve the institution’s performance in adhering to budget directives. Government institutions should fully and effectively implement GFMIS in all government units to enhance transparency and financial control. The GFMIS should also be configured in a way that meets the needs of the government unit in a way that enables it to record and track financial transactions and prepare financial reports in an accurate and timely manner.